C-Reactive Protein to Albumin Ratio Predict In-Hospital and Long-term Outcome of ST-Segment-Elevation Myocardial Infarction Patients with SARS-CoV2 Infection Underwent Fibrinolytic Therapy. - Jagannatha, Gusti Ngurah Prana; Artha, I Made Junior Rina; Pradnyana, I Wayan Agus Surya; Kamardi, Stanly; Kosasih, Anastasya Maria (Jurnal Kardiologi Indonesia, 2025)
In “C-Reactive Protein to Albumin Ratio Predict In-Hospital and Long-term Outcome of ST-Segment-Elevation Myocardial Infarction Patients with SARS-CoV2 Infection Underwent Fibrinolytic Therapy” (Indonesian Journal of Cardiology, 43(2), 64-76. https://doi.org/10.30701/ijc.1305), there is an error noted. An error has been found in the PDF version of this article. The DOI printed in the PDF is incorrect. The correct DOI is https://doi.org/10.30701/ijc.1305. The error occurs only in the PDF; the DOI listed in the article metadata is already correct. The publisher apologizes for any inconvenience caused by this error.DOI of original article: https://doi.org/10.30701/ijc.1305